An Induced Pluripotent Stem Cell‐Derived Neuromuscular Junction Platform for Study of the NGLY1‐Congenital Disorder of Deglycosylation. Issue 11 (19th August 2022) - Sasserath, Trevor; Robertson, Ashley L.; Mendez, Roxana; Hays, Tristan T.; Smith, Ethan; Cooper, Helena; Akanda, Nesar; Rumsey, John W.; Guo, Xiufang; Farkhondeh, Atena; Pradhan, Manisha; Baumgaertel, Karsten; et al.
Abstract: There are many neurological rare diseases where animal models have proven inadequate or do not currently exist. NGLY1 deficiency, a congenital disorder of deglycosylation, is a rare disease that predominantly affects motor control, especially control of neuromuscular action. In this study, NGLY1‐deficient, patient‐derived induced pluripotent stem cells (iPSCs) are differentiated into motoneurons (MNs) to identify disease phenotypes analogous to clinical disease pathology with significant deficits apparent in the NGLY1‐deficient lines compared to the control. A neuromuscular junction (NMJ) model is developed using patient and wild type MNs to study functional differences between healthy and diseased NMJs. Reduced axon length, increased and shortened axon branches, MN action potential (AP) bursting, and decreased AP firing rate and amplitude are observed in the NGLY1‐deficient MNs in monoculture. When transitioned to the NMJ‐coculture system, deficits in NMJ number, stability, failure rate, and synchronicity with indirect skeletal muscle stimulation are observed. This project establishes a phenotypic NGLY1 model for investigation of possible therapeutics and investigations into mechanistic deficits in the system. Abstract : NGLY1‐CDDG is a rare and recently identified congenital deglycosylation disorder that impairs motor function. Motoneurons (MNs) derived from NGLY1‐deficient patients are co‐cultured with skeletal muscle in a neuromuscular junction microphysiological system. Myotube contractile response from motoneuron stimulation in diseased and wild‐type systems are quantified and compared. Findings highlight the contribution of NGLY1‐deficient induced pluripotent stem cells MNs to neuromuscular dysfunction.